ANALYSIS OF EFFECTIVENESS OF ENTREPRENEURSHIP TRAINING ON INMATES IN BIMKER RUTAN KELAS 1 BANDUNG - Adriansyah, Muhammad; Wisesa, Anggara (Journal of Business and Management, 2017)
Abstract. Rutan Kelas 1 Bandung, as one of the Penitentiary, has one of the training places for the prisoners' entrepreneurial training called Bimker Rutan Kelas 1 Bandung. Preliminary research conducted in Bimker shows if there is a complaint from head manager related to the training activities undertaken by the participants. The manager felt that there was a discrepancy between the activities in entrepreneurship training with the purpose of the training being carried out. Therefore, this study aims to determine the factors causing the discrepancy between training activities with training objectives and understand and find solutions so that training can run effectively. This research uses the narrative method by understanding the perspective of resource based on the story (narrative) about entrepreneurship training delivered through the interview. The results of the evaluation of entrepreneurship training show that if trainees succeed in improving technical skills in certain areas of expertise, they feel that their entrepreneurial competence has not increased. Then the need for entrepreneurship training in Bimker is training for debriefing entrepreneurial competencies. The researcher recommends the solution for the training to be done with off-the-job training method in order to increase the entrepreneurship competence of the participants and they can show entrepreneurial activity with the competence they have.Â Keywords:Â  Bimker Rutan Kelas 1 Bandung, entrepreneurship, inmates, training, training effectiveness